Avaliação da composição química do solo, da produtividade e da composição bromatológica da forragem de Cynodon dactylon cv. vaquero submetida a doses crescentes de nitrogênio, aplicadas na forma de dejeto de suínos - Carvalho, João Paulo Fonesí de (2018)
The present research aimed to evaluate the response of productivity in dry matter composition of forage, mycotoxin (s) nutrient levels in dry mass and soil in grassland of Cynodon dactylon cv. Vaquero, subjected to doses increasing nitrogen, applied in the form of pig waste. The work was developed during the period November 2017 to March 2018, in the Experimental unit of the Pontifical Catholic University of Paraná, Toledo campus, located in the Western region of Paraná under latitude 24° 43 ' 13 '' S and longitude 53° 47 ' 01 "W. experimental design was of randomized blocks with six treatments (0, 50, 100, 150, 200, 250 kg ha-1) consisting of increasing doses of nitrogen in the form of pig manure, with five repetitions, totaling 30 plots. The experiment was initiated in November 2017, and the samples were carried out at the end of each of the four periods of cut, which had gaps between cuts of 30 days. Total productivity was studied of dry matter (kg ha-1), plant height (cm), crude protein (CP), dry matter (DM), neutral detergent fiber (NDF), acid detergent fiber (FDA), neutral detergent insoluble nitrogen (NIDN), acid detergent insoluble nitrogen (NIDA), lignin (LIG), ether extract (EE) and mineral matters (MM). Besides the mineral composition in dry matter and soil (organic matter, phosphorus, potassium, calcium, magnesium, manganese, zinc, iron). It was found that there was a positive linear effect of the treatments on dry matter productivity of forage, plant height, PB and EE that are increased as the doses of nitrogen rises, reaching the most expressive values at a dose of 250 kg ha-1. On the other hand, the levels of FDA, NIDA, NDF, NIDN and BOND decreased with the increase in levels of nitrogen. With increasing doses of N of pig waste occur increase in levels of nitrogen, phosphorus and potassium. The different nitrogenous doses applied in the form of pig waste in grass pasture vaquero, influence on composition and productivity of bromatological total dry matter, providing an increase in levels of PB, MS, EE, forage produced in four periods. The application of increasing doses of liquid waste pigs promotes increases in levels of nitrogen, phosphorus and potassium (g kg-1) in the dry matter of the aerial part of the shoot to the dose of 250 kg ha-1 of N in the form of pig waste. The application of pig waste as fertilizer reduces the concentration of organic matter, phosphorus, potassium, manganese and iron. MS grass productivity ranged from 3080.57 to 4520.57 Vaquero kg ha-1 in the air, that is, there is an estimated increase of 46.74% on MS productivity of Vaquero, when you go from 0 to 250 kg of waste per hectare.